Improvement of DFIG-based WECS performance using SMES unit - Khamaira, Mahmoud; Yunus, A.M. Shiddiq; Abu-Siada, Ahmed (AUPEC, 2013)
Doubly Fed Induction Generators (DFIGs) are widely used in variable speed wind turbine owing to its superior advantages that include ability to extract more energy from turbine, capability to control activeand reactive power independently and the usage ofreduced converter rating that reduces its overall cost.The application of DFIG in large wind energyconversion systems (WECS) has reached 55% of theworldwide total wind capacity during the year 2012. Onthe other side fluctuating output power, weak fault ridethrough capability and high sensitivity to griddisturbances are the main issues that affect DFIGperformance. In this paper, superconducting magneticenergy storage (SMES) unit is proposed to improve theoverall performance of a DFIG-based WECS duringvoltage sag disturbance in the grid side. A new controlapproach for SMES unit using hysteresis currentcontroller (HCC) along with proportional integral (PI) controller is introduced. Simulations results reveal the effectiveness of the proposed SMES controller in improving the overall performance of the WECS system under study.